Penanaman Nilai Karakter Disiplin Siswa Melalui Penerapan Pembiasaan di TK Ulumiyah Al Makruf Jombangan - Mustajib (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Children at an early age experience very rapid growth and development. This time is very appropriate to instill the first foundation to develop various potentials and abilities. Character discipline in children is also very important to be instilled because this character can not be formed instantly. As a teacher of The Children's Education Park must be patient in forming a disciplined character because this education is the initial stage and in this stage is the right stage in forming the character of discipline because the child is still at an early age, so it is necessary to instill the character of discipline in order to get used to adulthood. This research aims to describe the teacher's strategy in instilling the value of discipline character in students at Ulumiyah Al Makruf Jombangan Pare Kediri Kindergarten. This research uses a qualitative approach using descriptive methods. Data is collected using interview, observation, and documentation techniques to the parties concerned. The results of this study show that the strategies carried out by teachers in instilling the character of discipline are quite good, although there are still many obstacles that inhibit in forming a sided character